Wortschatzerinnerungskarte: Menguasai Bahasa melalui Kosa Kata - Rofi'ah, Rofi'ah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The study aimed to describe the use of *Wortschatzerinnerungskarte* as an instructional medium of teaching German as a foreign language and the results of its use in the classroom. The study was designed to promote longer vocabulary retention to learners of German as a foreign language. This was a descriptive quantitative study that used quantitative data to support the analysis of qualitative data. The researcher was the main instrument of the study. The other instruments used were an observation sheet, test, and questionnaire. The result of the study revealed that the use of *Wortschatzerinnerungskarte* improved the students’ learning motivation. Moreover, this instructional medium can help the students remember the vocabulary better and boost up their learning performance.